Pengukuran Perencanaan Strategis Sistem Informasi Pada Universitas Sjakhyakirti - Ade Sukma Wati; Mariana Purba; Nia Umilizah; Lemi Iryani (JSAI (Journal Scientific and Applied Informatics), 2024)
This study examines the performance of information systems at Unisti based on aspects of Corporate Contribution, User Orientation, Operational Excellence, and Future Orientation. By achieving level 4.0 in several aspects, Unisti has succeeded in making a positive impact through the implementation of IT systems that improve operational efficiency, user satisfaction, and the future vision of the university. Nonetheless, user evaluations also identify some shortcomings that need to be addressed and improved to achieve excellent IT/SI quality. Awareness of the need for continuous evaluation and future innovation is key in ensuring that IT/SI remains an effective tool in supporting the achievement of the university's vision and mission. IT implementation at Sjakhyakirti University as a whole achieved an adequate level of achievement, with 75% from the perspective in the IT Balanced Scorecard considered to have been well implemented